Effectiveness Of Beetroot And Spinach Against The Increase In Hemoglobin Levels Of Pregnant Women In The Primary Clinic Kasih Bunda, 2022 - Istiqomah, Wahyu; Achmad Fauzi (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2022)
Aims: Pregnant women who suffer from anemia are at risk of miscarriage, premature birth, low birth weight babies, and bleeding before and after delivery. Purpose: It is known the effectiveness of giving beetroot and spinach to increase hemoglobin levels in pregnant women in primary clinics in 2022. Methods: One-group "quasi-experiment" Designing a test with a pre- and post-test. Quasi-experimental studies are a type of experimental research that omits the use of a control group. Result: The average hemoglobin level of pregnant women before consuming beetroot is 10.8 gr / dl and after consuming beets 11.9 gr / dl 200 gr every day for 28 days the average hemoglobin level increases to 12.3 gr / dl. The average hemoglobin level of pregnant women before consuming spinach is 10.2 gr / dl and after consuming spinach every day for 28 days the average hemoglobin level increases to 11.4 gr / dl. With a maximal number of 11.9 gr / dl, the p value >0.05 Conclusion and Advice: Beetroot and spinach consumption is associated with increased hemoglobin levels in pregnant women and offers a safe and healthy alternative to fe tablets for women who may suffer from their uncomfortable side effects, such as nausea, vomiting, constipation, heartburn, and stomach cramps. Pregnant women with anemia are often advised to eat beets or spinach every day so that their hemoglobin levels can rise as quickly as possible.